2013
DOI: 10.1007/s00540-013-1638-0
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative peritonsillar infiltration of dexamethasone and levobupivacaine reduces pediatric post-tonsillectomy pain: a double-blind prospective randomized clinical trial

Abstract: Addition of dexamethasone to levobupivacaine for preoperative peritonsillar infiltration has better postoperative analgesic effects than i.v. dexamethasone combined with peritonsillar levobupivacaine infiltration in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 28 publications
1
23
0
3
Order By: Relevance
“…Kasapoglu et al found a significant difference between their levobupivacaine group and their control group in terms of the time to first analgesic request [ 3 ]. In our study, similar to the findings of Basuni et al, the times to first analgesic request in groups L and LA were 379.1 ± 172.3 and 383.8 ± 173.5 minutes, respectively [ 27 ]. In our opinion, these times were longer because levobupivacaine is a long-acting LA, but levobupivacaine with the addition of adrenaline did not alter the analgesic requirement time.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Kasapoglu et al found a significant difference between their levobupivacaine group and their control group in terms of the time to first analgesic request [ 3 ]. In our study, similar to the findings of Basuni et al, the times to first analgesic request in groups L and LA were 379.1 ± 172.3 and 383.8 ± 173.5 minutes, respectively [ 27 ]. In our opinion, these times were longer because levobupivacaine is a long-acting LA, but levobupivacaine with the addition of adrenaline did not alter the analgesic requirement time.…”
Section: Discussionsupporting
confidence: 91%
“…For this reason, in our study, we used acetaminophen for postoperative pain relief. In a study that presented the dependence of time to first analgesic request on perioperative LA infiltration, Basuni et al measured the time to first analgesic request to be 373.2 ± 63.6 minutes when they used levobupivacaine [ 27 ]. Kasapoglu et al found a significant difference between their levobupivacaine group and their control group in terms of the time to first analgesic request [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies indicate that smoking cessation may reduce postoperative complications following craniotomy 38 . Secondly, numerous studies have shown that scalp infiltration in patients undergoing craniotomies play crucial roles in post-craniotomy pain management 39 - 43 . Accordingly, scalp infiltration with ropivacaine or bupivacaine in the ERAS protocol may reduce the incidence and severity of postoperative pain, which has also been shown in other studies 32 , 44 , 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Some studies indicate that smoking cessation may reduce postoperative complications following craniotomy 28 . Secondly, numerous studies have shown that scalp infiltration in patients undergoing craniotomies play crucial roles in post-craniotomy pain management [29][30][31][32][33] . Accordingly, scalp infiltration with ropivacaine or bupivacaine in the ERAS protocol may reduce the incidence and severity of postoperative pain, which has also been shown in other studies 23,34 .…”
Section: Development Of Standardized Pain Management and Eras Protocomentioning
confidence: 99%